Ferrochrome Smelting And Smelting Capacity Investment In Zimbabwe - J. Chirasha (The Southern African Institute of Mining and Metallurgy, 2011)
Keywords: Pyrometallurgy, ferrochrome, smelting, investment, Zimbabwe Four smelting plants currently make up the ferrochrome smelting capacity in Zimbabwe. Zimbabwe Alloys and Zimasco represent more then ninety per cent of Zimbabwe?s ferrochrome smelting capacity, while Maranatha and Oliken contribute the difference. Very limited investment in the sector (even for the expansion of existing smelters) has been experienced over many years, despite the fact that about 95% of the world?s chrome ore resources are in the Bushveld Igneous Complex of South Africa and the Great Dyke of Zimbabwe. The Bushveld has a greater quantity but a lower grade than the Great Dyke. A ten per cent increase in Zimbabwean ferrochromium production has been recorded in the past ten years, showing an almost stagnant capacity investment.